2007
DOI: 10.2174/092986707779941023
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Affinity Determinants for Ligand Binding to the Aromatic Amino Acid Hydroxylases

Abstract: Hydroxylation of the aromatic amino acids phenylalanine, tyrosine and tryptophan is carried out by a family of non-heme iron and tetrahydrobiopterin (BH4) dependent enzymes, i.e. the aromatic amino acid hydroxylases (AAHs). The reactions catalyzed by these enzymes are important for biomedicine and their mutant forms in humans are associated with phenylketonuria (phenylalanine hydroxylase), Parkinson's disease and DOPA-responsive dystonia (tyrosine hydroxylase), and possibly neuropsychiatric and gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 115 publications
(177 reference statements)
2
64
0
Order By: Relevance
“…5,17 Our results suggest several therapeutic targets including NOTCH1, IGFR1, and cathepsin B. 18,19 Our study also suggests that the expression of certain targets, such as PDGFRB and androgen receptor, may not be worth pursuing.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…5,17 Our results suggest several therapeutic targets including NOTCH1, IGFR1, and cathepsin B. 18,19 Our study also suggests that the expression of certain targets, such as PDGFRB and androgen receptor, may not be worth pursuing.…”
Section: Discussionmentioning
confidence: 79%
“…One study 7 concluded that although the sensitivity of formalin-fixed and paraffin-embedded tissue profiling was low (B50%), when compared with frozen tissue, the specificity (95%) and positive predictive value (92%) were high. In another study, 18 high correlation (R 2 between 0.82 and 0.89) of profiling data between frozen and formalin-fixed and paraffin-embedded tissue tissue was identified in tumors from the lung and colon. Our formalin-fixed and paraffin-embedded tissue profiling study identified 96 differentially expressed genes between small intestinal and rectal neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although a number of molecular genetic studies have been performed on different genes involved in serotonergic neurotransmission [Haddley et al, 2008;Russo et al, 2007], the precise clinical correlates of either reduced or excessive serotonergic neurotransmission are unknown. Tryptophan hydroxylase (TPH) is responsible for the 5-hydroxylation of L-tryptophan (L-Trp), which is the rate-limiting step in 5-HT biosynthesis and the first step in melatonin production [Teigen et al, 2007]. Two different TPH enzymes (TPH1 and TPH2) are expressed by two distinct genes: TPH1 (MIM] 191060) appears to be mainly expressed in nonneuronal serotonergic cells, for example, skin, pineal gland, and enterochromaffin cells [Slominski et al, 2005]; whereas TPH2 (MIM] 607478) is expressed in neuronal serotonergic cells, for example, serotonergic neurons of the brain and gut [Cote et al, 2003;Gutknecht et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…The TPH enzymes belong to a superfamily of aromatic amino acid hydroxylases (AAAH). They are iron-and tetrahydrobiopterin (BH 4 )-dependent monooxygenases; that is, one atom of O 2 , is incorporated into the respective amino acid substrates, whereas the other is ultimately reduced to water [Teigen et al, 2007]. Crystal structures of the catalytic domain of all three AAAH enzymes have shown that they all possess a mononuclear nonheme iron binding motif, referred to as the 2-His-1-carboxylate facial triad, which is conserved in TPH2: His318, His323, and Glu363 [Hegg and Que, 1997;Wang et al, 2002].…”
Section: Introductionmentioning
confidence: 99%